Marasmioid and Gymnopoid Fungi of the Republic of Korea. 8. Gymnopus Section Levipedes - Ryoo, Rhim; Antonín, Vladimír; Ka, Kang-Hyeon (Mycobiology, 2020)
Collections of Gymnopus sect. Levipedes from the Republic of Korea have been studied. Two new species, Gymnopus dryophiloides and G. brunneodiscus , are described based on their macro- and micromorphological and phylogenetic characteristics. Three other species, referred to as Gymnopus spp. 1, 2, and 3, are distinguished as separate taxa without formal descriptions. Taxonomic and phylogenetic positions of all taxa have been inferred and confirmed by analyses of ITS and LSU sequence data. Their detailed descriptions, illustrations and an identification key are provided.
Keywords: Omphalotaceae; new taxa; ITS; molecular systematics; LSU